Interkoneksi Volatilitas Nilai Tukar Dan Tujuan Domestic Impossible Trinity Pada Asean-4: Dornbusch Overshooting Model - Lilis Yuliati; Fendi Indra Sujianto; Aisah Jumiati (Trunojoyo University of Madura, 2018)
The purpose of this research is to identify the issues of becoming of the volatility of the exchange rate that is seen the theory of exchange rate overshooting by Dornbusch with the assumptions that goods prices are sticky. Then implicates in determining the monetary policy framework in a country known as the impossible trinity. Impossible Trinity consists of three the policy are not fully always dominant used simultaneously, namely the stability of exchange rates, the mobility of capital flows (FDI), and monetary independent policy, namely GDP, inflation, and the interest rate. The research period lasts 1987Q1-2016Q4 with the country which became the object of Indonesia, Malaysia, Thailand, and the Philippines. In this research model is the model Dynamic Vector Error Correction models (VECM) models.The result of the analysis indicate that all countries experienced the phenomenon of overshooting. Then in the determination of policies Monetary found, that Indonesia puts more emphasis on inflation and GDP, Malaysia on interest rates and Foreign Direct Investment, Thailand on inflation and interest rates and Philippines on exchange rate and GDP trails through inflation. Exchange rate overshooting determines of the monetery policy that depend on the characteristic and economic priority of a countries.